Penerapan Alat Bukti Petunjuk Oleh Hakim Dalam Menjatuhkan Putusan Tindak Pidana Pembunuhan - Broto Priyono; Fadjrin Wira Perdana; Irwan Irwan; Doharman Lumban Tungkup; Miran Miran (CV. Publikasi Indonesia, 2022)
Every Indonesian citizen has the right to live and continue his life. Unfortunately, criminal acts that violate the right to life of citizens still occur even though this has been regulated firmly in the Criminal Code chapter XIX articles 338-350, such as acts of murder that are still carried out by citizens against other citizens. . If this is allowed, then the name of the rule of law is just a name without any act of justice that can deter and minimize crime. Judges as decision-makers in court certainly have an important role in upholding justice, but judges' decisions must be strengthened by various evidences. Therefore, the researcher wants to find out more about the application of evidence guided by the judge in passing the verdict on the crime of murder. The purpose of this study is to determine the important role of evidence guided by judges in making court decisions against the crime of murder. The research method used is descriptive qualitative with interview, documentation, and observation techniques at Court X in city Y. After the data is obtained, it can be analyzed to find out the results of the study which show that evidence indicates an important role for judges in deciding a criminal case. homicide by 80%. With this, the other 20% is influenced by other factors, both internal and external factors.